2006
DOI: 10.1021/np060006n
|View full text |Cite
|
Sign up to set email alerts
|

Cyclic Heptapeptides from the Jamaican Sponge Stylissa caribica

Abstract: Two new cyclic heptapeptides, stylisin 1(1) and stylisin 2 (2), were isolated and characterized from the Jamaican sponge Stylissa caribica, in addition to the cyclic heptapeptide phakellistatin 13 (3) and the known bromopyrrole alkaloids sceptrin (4), stevensine (5), and oroidin (6). The new structures were assigned on the basis of 1D and 2D NMR spectroscopic data, as well as chemical methods for the elucidation of the absolute configuration of amino acids. The peptides and alkaloids have been evaluated for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
52
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(53 citation statements)
references
References 29 publications
1
52
0
Order By: Relevance
“…Stylissa massa belongs to the family Dictyonellidae, which is one of the better investigated groups of marine invertebrates from the perspective of natural products chemistry, and some of the identified compounds have known ecological roles (Becerro et al, 2003). The most prominent natural products isolated from S. massa include the alkaloids oroidin, debromohymenialdisine, hymenialdisine (Tasdemir et al, 2002), sceptrin (Mohammed et al, 2006), hymenidin (Kobayashi et al, 1986), and palau'amine (Kinnel et al, 1993). The aim of this study was to assess the variation in secondary metabolite production in S. massa at various spatial scales, including local, regional, and biogeographic.…”
Section: Introductionmentioning
confidence: 99%
“…Stylissa massa belongs to the family Dictyonellidae, which is one of the better investigated groups of marine invertebrates from the perspective of natural products chemistry, and some of the identified compounds have known ecological roles (Becerro et al, 2003). The most prominent natural products isolated from S. massa include the alkaloids oroidin, debromohymenialdisine, hymenialdisine (Tasdemir et al, 2002), sceptrin (Mohammed et al, 2006), hymenidin (Kobayashi et al, 1986), and palau'amine (Kinnel et al, 1993). The aim of this study was to assess the variation in secondary metabolite production in S. massa at various spatial scales, including local, regional, and biogeographic.…”
Section: Introductionmentioning
confidence: 99%
“…7 Sceptrin was evaluated against D6 and W2 strains by other authors and showed no activity. 32 In conclusion, this chemical study underscores the presence of bromopyrrole alkaloids as the representative secondary metabolites of Agelas cerebrum, and contributes to the chemotaxonomy within the Agelasidae family. Studies are in progress in order to advance the evaluation of the in vivo antimalarial activity of bromopyrrole alkaloids from Agelas cerebrum.…”
mentioning
confidence: 60%
“…The pseudomolecular ion cluster for the compound at m/z 825/ 827/829/831/333/835 was indicative of a chlorotetrabrominated compound. There are at least two B-P-2-AI compounds published with this molecular weight: konbu'acidin B 3 (8) and tetrabromostyloguanidine (9). 33 MS-MS analysis of this ion cluster obtained directly from the tissue slice yielded fragments 18, 251 and 269 amu smaller than the parent indicating loss of water, a dibromopyrrole carboxylate and water and dibromopyrrole carboxylate respectively.…”
Section: Maldi-imaging Detection Of B-p-2-ais In S Flabellata Sectionsmentioning
confidence: 99%